2017
DOI: 10.1039/c6np00097e
|View full text |Cite
|
Sign up to set email alerts
|

Chemical mediation as a structuring element in marine gastropod predator-prey interactions

Abstract: Covering: up to 2017Chemical mediation regulates behavioral interactions between species and thus affects population structure, community organization and ecosystem function. Among marine taxa that have developed chemical mediation strategies, gastropods belong to a diverse group of molluscs found worldwide, including species with a coiled, reduced or absent shell. Most gastropods use natural products to mediate a wide range of behaviors such as defense, prey location or interactions with con- and hetero-gener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 227 publications
0
45
0
1
Order By: Relevance
“…This behavioural effect may be related to a reduction in chemosensory ability, as reported in previous studies where elevated pCO 2 levels was found to interfere with neurotransmitter receptor function, potentially GABA A -like receptors, thus compromising behaviour of snails 11,53 and marine fishes 54 . Furthermore, in gastropods, a wide range of behaviours, including foraging, are mediated by chemical compounds known as secondary metabolites, and S. striatus are known to use the secondary metabolites produced by Lyngbya majuscula in foraging 55 . As such, disruption to decision-making may have arisen either from the compromised detection of stimulus cues (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…This behavioural effect may be related to a reduction in chemosensory ability, as reported in previous studies where elevated pCO 2 levels was found to interfere with neurotransmitter receptor function, potentially GABA A -like receptors, thus compromising behaviour of snails 11,53 and marine fishes 54 . Furthermore, in gastropods, a wide range of behaviours, including foraging, are mediated by chemical compounds known as secondary metabolites, and S. striatus are known to use the secondary metabolites produced by Lyngbya majuscula in foraging 55 . As such, disruption to decision-making may have arisen either from the compromised detection of stimulus cues (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…The second phase involves biotransformation to enhance the hydrophilicity of molecules controlled by enzymes to promote glucuronidation, sulfonation, acetylation, methylation and conjugation with amino acids and glutathione. Eventually in phase three, molecules are transferred through cell membranes by transporter proteins for excretion [6].…”
Section: Halogenated Secondary Metabolites Of Aplysia Dactylomela Rangmentioning
confidence: 99%
“…In cuparane-type compounds, three methyls are present in the aliphatic portion at positions 1, 2 and 2, while in laurane-type compounds, the three methyls in the aliphatic portion are located at positions 1, 2 and 3 [34]. A study on the halogenated metabolites of Aplysia dactylomela Rang initiated with the isolation of brominated laurane type compounds, aplysin (4) and aplysinol (5) [35]; their source of origin remained unknown until Irie and co-workers (1966) isolated the laurane-type sesquiterpene laurinterol (6) from Laurencia intermedia [36]. Most sesquiterpenes are ecologically important as anti-epibiosis agents [19].…”
Section: Cuparane and Laurane Skeletonmentioning
confidence: 99%
See 1 more Smart Citation
“…In marine organisms, study of metabolome variability mostly focused on so-called secondary or specialized metabolites (Kuhlisch and Pohnert 2015), low molecular weight (< 1500 Da) molecules playing key roles in various ecological processes (Agrawal et al 2012;Zimmer 2013, 2012). These metabolites being involved in chemical mediation between organisms, their variation does not only affect the resilience of one species but it can have cascading effects on the networks of interactions (Hay 2014;Bornancin et al 2017). Intraspecific variation of metabolites with time and space is crucial for understanding species ecology and ecosystem functioning (Paul et al 2007;Glassmire et al 2016).…”
Section: Introductionmentioning
confidence: 99%